Translation Error In Advertisements - Kartina Rahmadhani Rambe; Meisuri; I Wayan Dirgayasa Tangkas; Winda Setiasari; Susi Damaiyanti (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
The researcher intends to conduct a study to examine advertisement banners that have an error in translating or modifying the word from source language to target language. the research is to investigate the many sorts of translation errors in advertisement banners. The study concentrated on the incorrect translation of source language to target language that occurred in advertising. This research is classified as Descriptive Qualitative Research. Qualitative research is a descriptive method in which data is collected in the form of written or spoken words. The data was collected from 20 public signs in Medan by the researcher. These public signs display the name of the service to the public. After assessment the data, it was discovered that translation error is 70% in spelling mistakes, 10% in grammatical errors, 15% in vocabulary misspellings, and 5% in punctuation. The greatest percentage is found in spelling errors. In the interview section, spelling mistakes and vocabulary misspellings occurred because they did not know how to produce the correct word due to a lack of vocabulary in English. Grammatical errors occurred because they did not know how to arrange the words correctly, and punctuation is the lowest error since it is not difficult to know how to apply proper punctuation in text